Cachorr@404: Peer-Instruction Practices During Quarantine Times - Kohler-Casasempere, J; Chourio-Acevedo, L (IEEE Computer Society, 2020)
Student attrition is a long-lasting problem which affects higher education institutions around the world. In the Chilean context, this phenomenon needs to be addressed, as it is considered for university accreditation and undergraduate education quality assessment the rather high drop-out rate of first-year students at the Departamento de Ingenieria Informatica of Universidad de Santiago de Chile has led to the creation of Ca-chor@404, a peer-instruction based accompaniment programme which supports incoming students by providing tutorials on key subjects and assisting them in their adaptation to university life. To succeed, the programme is led by a multidisciplinary team and considers different aspects of first-year student needs the current Covid-19 pandemic, with its associated quarantine, has redefined some key aspects of university life adaptation, thus forcing Cachorr@404 to adjust to the new context the adaptation process has turned into a learning experience regarding the use of new technologies to support the teaching-learning process within the programme s initial courses. This article attempts to describe this accompaniment programme, emphasising key issues that emerged from the global contingency. © 2020 IEEE.